EVALUASI PENERAPAN ZONA SELAMAT SEKOLAH PADA BEBERAPA FUNGSI JALAN DI YOGYAKARTA - Susanto, Benidiktus; Jon, Jackrois Antros Sustrial (FSTPT Indonesia, 2015)
School Safety Zones (ZoSS) which has been implemented in several schools in Yogyakarta are not functioning optimally. These facilities aim to reduce vehicle speed when crossing on this zone, so that the safety of the people who crossed on this zone will increase, especially for school children. In Indonesia, the roads are designed with different functions with different speed limit, so it is important to study the performance of these ZoSS facilities on the each road function. This study compares the speeds of vehicles in ZoSS on each road functions and characteristics of pedestrian when they cross the road. The results of this study showed that the speed of vehicles on each road functions are still above the expected maximum speed at ZoSS set by the Ministry of Transportation. The majority of pedestrian behavior in an unsafe condition.